A longitudinal assessment of work situation, sick leave, and household income of mothers and fathers of children with cancer in Sweden. (August 2013) - Hovén, Emma; von Essen, Louise; Norberg, Annika Lindahl
Abstract Background. The diagnosis of childhood cancer often results in an altered life situation for the parents, characterized by difficulties regarding work, family and household demands. Previous research shows that parents' work situation and income are impacted, yet, few studies have explored the issue from a longitudinal perspective. This study sought to increase the knowledge about the socio-economic conditions of parents of children with cancer in Sweden by means of a longitudinal assessment of work situation, sick leave, and household income. Material and methods. The sample consisted of mothers (n = 139) and fathers (n = 138) of children with cancer recruited from 2002 to 2004. Data was collected by telephone interviews at six time points, ranging from the time of diagnosis to one year after the end of treatment. Results. Findings showed that parents' work situation was most evidently impacted during the child's treatment, when the greatest proportions of non-working and sick-listed parents were found. Compared with the time of diagnosis, fewer mothers worked up to three months after the end of treatment, and more mothers were on sick leave one year after the end of treatment. Although the extent of sick leave among fathers did not differ compared with the time of diagnosis, fewer fathers worked one year after the end of treatment. Household income was significantly reduced during the child's treatment and months thereafter, while income was at an equal level as before the diagnosis for most families one year after the end of treatment. Conclusion. The results offer a unique understanding of how mothers' and fathers' work situation and income are impacted in the short- and long-term, and give guidance on how to improve the comprehensive support given to parents of children with cancer. Socio-economical issues should be emphasized as these may provide targets for policy interventions aiming to reduce parental strain related to work and finances.